Metabarcoding Analysis of Bacterial Communities Associated with Media Grow Bed Zones in an Aquaponic System - Kasozi, Nasser; Kaiser, Horst; Wilhelmi, Brendan (International journal of microbiology, 2020)
)e development of environmentally sustainable plant and fish production in aquaponic systems requires a complete understanding of the systems’ biological components. In order to better understand the role of microorganisms in this association, we studied the bacterial communities in the dry, root, and mineralized zones of a flood-and-drain media bed aquaponic system. Bacterial communities were characterized using metabarcoding of the V3-V4 16S rRNA regions obtained from paired-end Illumina MiSeq reads. Proteobacteria, Actinobacteria, and Bacteroidetes accounted for more than 90% of the total community in the dry zone and the effluent water. )ese phyla also accounted for more than 68% of the total community in the root and mineralized zones. )e genera Massilia, Mucilaginibacter, Mizugakiibacter, and Rhodoluna were most dominant in the dry, root, and mineralized zones and in the effluent water, respectively. )e number of shared operational taxonomic units (OTUs) for the three zones was 241, representing 7.15% of the total observed OTUs. )e number of unique OTUs in samples from dry zone, root zone, mineralized zone, and effluent water was 485, 638, 445, and 383, respectively.)e samples from the root zone harbored more diverse communities than either the dry or mineralized zones. )is study is the first to report on the bacterial community within the zones of a flood-and-drain media bed. )us, this information will potentially accelerate studies on other microbial communities involved in the bioconversion of nitrogen compounds and mineralization within these types of aquaponic systems.
Keywords: Metabarcoding; Bacterial Communities; Aquaponic System